Assessment of the Needs of Rural Older People in Bangladesh. Issue 3 (September 2022) - Ali, Isahaque; Azman, Azlinda; Ahmed, Manzur Kadir; Akhtar, Tahmina; Deceukelier, Bruno
The objective of this study is to examine the needs of older population in rural Bangladesh. Through a purposive sampling, 80 participants were selected from eight villages located in eight administrative districts. In-depth interviews were conducted to collect some quantitative and mostly qualitative data. The study findings indicated that the majority of rural older people were in abject poverty, had limited social security and suffered from ill health, malnutrition, and inadequate medical and general health services. Also, they lacked steady income, had lost family relations, suffered from social isolation and loneliness, and are dependent on others. Due to loss of family relations, they lacked caregivers and had little or no social status and position, thus making them susceptible to depression, frustration and stress. Moreover, they have limited access to recreational and transportation facilities, as well as community-based support programmes. Our findings suggest implementation of social security and protection schemes in the rural area and extension of adequate and quality health care facilities to the rural older. In summary, rural older people in Bangladesh need a more balanced and integrated social and medical care policies to maintain a decent quality of life.